2015
DOI: 10.1007/s10853-015-9099-5
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of tribofilm characteristics on the running-in behavior of aluminum–silicon alloys

Abstract: In this study, we evaluate the evolution of the interfacial processes in metallic sliding contacts (i.e., aluminum alloys) in terms of their elemental composition, structural changes, and nanomechanical properties in order to understand the optimal running-in behavior leading to steady-state low friction and high wear resistance. Two different sliding conditions are used, resulting in low and high long-term friction and corresponding well with the low and high wear rates. Ex situ elemental analysis of these sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 37 publications
2
6
0
Order By: Relevance
“…A nano indention hardness mapping was also performed which does not show conclusive trends as the alloy consists of a dual phase microstructure with very different hardness values of each phase and therefore the scatter in the hardness in the base material is very high, which makes it difficult to observe the trend in the hardness change due to deformation. A very high scatter was also observed by Stoyanov et al 41 . Stoyanov et al observed the change in nanomechanical properties of the shear deformed layer by tribometer as a function of contact pressure and observed that the lower pressure (15 MPa) showed a much higher degree of mechanical mixing and grain refinement compared to the higher pressure of 35 MPa in Al-Si alloy 41 .…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…A nano indention hardness mapping was also performed which does not show conclusive trends as the alloy consists of a dual phase microstructure with very different hardness values of each phase and therefore the scatter in the hardness in the base material is very high, which makes it difficult to observe the trend in the hardness change due to deformation. A very high scatter was also observed by Stoyanov et al 41 . Stoyanov et al observed the change in nanomechanical properties of the shear deformed layer by tribometer as a function of contact pressure and observed that the lower pressure (15 MPa) showed a much higher degree of mechanical mixing and grain refinement compared to the higher pressure of 35 MPa in Al-Si alloy 41 .…”
Section: Resultssupporting
confidence: 73%
“…A very high scatter was also observed by Stoyanov et al 41 . Stoyanov et al observed the change in nanomechanical properties of the shear deformed layer by tribometer as a function of contact pressure and observed that the lower pressure (15 MPa) showed a much higher degree of mechanical mixing and grain refinement compared to the higher pressure of 35 MPa in Al-Si alloy 41 .…”
Section: Resultssupporting
confidence: 73%
“…The rheology and flows of the third bodies for macroscopic tribology has been described in detail by Descartes et al [ 44 ] and subsequently applied in other tribological systems [ 45 , 46 ]. The authors describe the source flow of the third body (i.e., material trapped in-between the first bodies, not including the ‘structural tribological transformation’ or thermal tribological transformation’ zone) in a natural and artificial form, being formed from an internal and an external source respectively.…”
Section: What Is Microtribology?mentioning
confidence: 99%
“…Some authors have reported that the friction and wear properties of silicon-containing aluminum alloys improve through the reduction of friction and/or wear, known as running-in [23,26]. For example, Shioda et al [23] reported that by controlling the size and area ratio of the silicon grains, the friction system between bearing steel (AISI52100) and siliconcontaining aluminum alloy could exhibit running-in without an increase in the silicon content.…”
Section: Introductionmentioning
confidence: 99%